2019
DOI: 10.1063/1.5119905
|View full text |Cite
|
Sign up to set email alerts
|

Similarities between the structure functions of thermal convection and hydrodynamic turbulence

Abstract: In this paper, we analyze the scaling of velocity structure functions of turbulent thermal convection. Using high-resolution numerical simulations, we show that the structure functions scale similar to those of hydrodynamic turbulence, with the scaling exponents in agreement with She and Leveque's predictions [Phys. Rev. Lett. 72, 336-339 (1994)]. The probability distribution functions of velocity increments are non-Gaussian with wide tails in the dissipative scales and become close to Gaussian in the inertia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 57 publications
(84 reference statements)
2
8
0
Order By: Relevance
“…In turbulent convection, buoyancy injects kinetic energy at all scales, including the dissipation range. Bhattacharya et al [50] showed that for Pr = 1 convection, although the modal kinetic energy injection by buoyancy is small at intermediate wavenumbers (as discussed earlier), it adds up to a significant fraction of the total kinetic energy injection when summed over the inertial and dissipative scales.The inertial-range kinetic energy flux is due to the fraction of energy injected only at large scales and hence less than the total kinetic-energy dissipation rate. We expect the kinetic-energy dissipation rate and the energy injection rates by buoyancy to exhibit a similar Pr dependence as the energy flux.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…In turbulent convection, buoyancy injects kinetic energy at all scales, including the dissipation range. Bhattacharya et al [50] showed that for Pr = 1 convection, although the modal kinetic energy injection by buoyancy is small at intermediate wavenumbers (as discussed earlier), it adds up to a significant fraction of the total kinetic energy injection when summed over the inertial and dissipative scales.The inertial-range kinetic energy flux is due to the fraction of energy injected only at large scales and hence less than the total kinetic-energy dissipation rate. We expect the kinetic-energy dissipation rate and the energy injection rates by buoyancy to exhibit a similar Pr dependence as the energy flux.…”
Section: Introductionmentioning
confidence: 84%
“…Consequently, Π u < u . Bhattacharya et al [50] showed that for Pr = 1, the inertial-range kinetic energy flux is approximately one-third of the total dissipation rate. In this subsection, we will describe these quantities for various Prandtl numbers.…”
Section: B Energy Flux and Viscous Dissipation In Thermal Convectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies, however, show that these rates get an additional correction of approximately Ra −0.2 for Pr ∼ 1 10,26,29,30,44,45 . The above correction is because of the inhibition of nonlinear interactions due to the presence of walls and buoyancy 6,29,30,57 . In addition, the above studies reveal that the thickness of the viscous boundary layer in RBC deviates from Re −1/2 , contrary to what is assumed in GL model 44,58,59 .…”
Section: B Revised Grossmann-lohse (Rgl) Modelmentioning
confidence: 99%